Differentially expressed gene transcripts in roots of resistant and susceptible chickpea plant (Cicer arietinum L.) upon Fusarium oxysporum infection - Nimbalkar, Suhas B.; Harsulkar, Abhay M.; Giri, Ashok P.; Sainani, Mohini N.; Franceschi, Vincent R.; Gupta, Vidya S. (Physiological and Molecular Plant Pathology, 2006)
Differentially expressed genes in chickpea, (Cicer arietinum L.) during root infection by Fusarium oxysportan f sp. ciceri Racel, were identified using cDNA-RAPD and cDNA-AFLP approaches. The former employed decamer primers on cDNA template and revealed nine differentially expressed transcripts in the resistant-infected chickpea variety. Among the 2000 transcript-derived fragments (TDFs) screened by cDNA-AFLP, 273 were differentially expressed in chickpea roots during Fusaritan infection. Only 13.65% of the TDFs were differentially regulated during pathogen challenge, while the other 86% were expressed non-differentially during the process of pathogen infection in chickpea roots. Nineteen TDFs, which expressed differentially in the resistant-infected chickpea variety were cloned and sequenced. Two of these TDFs were similar to transcription factors like WRKY proteins and 14-3-3 proteins, while three TDFs represented the NBS-LRR-type gene sequences. Two TDFs had sequence identity to genes known to have function in defense. The RAPID TDF CaFRi60 showed sequence identity to gamma-glutamyl-cysteine synthetase. Among the TDFs examined by cDNA-AFLP, 19 were confirmed by Reverse Northern blot to be differentially expressed. The data confirms the effectiveness of the cDNA-AFLP technique in detecting differentially expressed genes during pathogenesis. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: cDNA-AFLP; Chickpea; Cicer arietinum; differentially expressed genes; fusarium oxysporum; Transcriptome

Diverse forms of pin-II family proteinase inhibitors from capsicum annuum adversely affect the growth and development of helicoverpa armigera - Tamhane, Vaijayantl A.; Giri, Ashok P.; Sainani, Mohini N.; Gupta, Vidya S. (Gene, 2007)
Novel forms of Pin-II type proteinase inhibitor (PIs) cDNAs (CanPIs) having three or four inhibitory repeat domains (IRD) were isolated from the developing green fruits of Capsicum annuum. Deduced amino acid (aa) sequences of the CanPIs showed up to 15% sequence divergence among each other or reported inhibitors (CanPI-1 AF039398, CanPI-2 AF221097). Amino acid sequence analysis of these CanPIs revealed that three IRD Pls have trypsin inhibitory sites, while four IRD CanPIs have both trypsin and chymotrypsin inhibitory sites. Four CanPIs, two having three IRD (CanPI-3 AY986465 and CanPI-5 DQ005912) and two having four IRD (CanPI-7 DQ005913 and CanPI-9 DQ005915), were cloned in Pichia pastoris to express recombinant CanPIs. Recombinant CanPIs inhibited 90% of bovine trypsin (TI), while chymotrypsin inhibition (0) varied with the number of chymotrypsin inhibitory sites in the CanPIs. Recombinant inhibitors inhibited over 70% of the gut proteinase activity of Helicoverpa armigera. H. armigera larvae fed on recombinant CanPIs individually incorporated into artificial diet, showed 35% mortality; in addition, weight gain in H. armigera larvae and pupae was severely reduced compared to controls. Of the four CanPIs, CanPI-7, which has two sites for TI and CI, was the only one to have a consistently antagonistic effect on H. armigera growth and development. We conclude that among the four recombinant Pls tested, CanPIs containing diverse IRDs are best suited for developing insect-resistant transgenic plants. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: insect resistance; IP repeats; PI-insect interaction; Pichia pastoris; potato type 2 inhibitors (Pot-II); Solanaceae

Digestive duet: midgut digestive proteinases of manduca sexta ingesting nicotiana attenuata with manipulated trypsin proteinase inhibitor expression - Zavala, Jorge A.; Giri, Ashok P.; Jongsma, Maarten A.; Baldwin, Ian T. (Plos One, 2008)
Background: The defensive effect of endogenous trypsin proteinase inhibitors (NaTPIs) on the herbivore Manduca sexta was demonstrated by genetically altering NaTPI production in M. sexta's host plant, Nicotiana attenuata. To understand how this defense works, we studied the effects of NaTPI on M. sexta gut proteinase activity levels in different larval instars of caterpillars feeding freely on untransformed and transformed plants. Methodology/Principal Findings: Second and third instars larvae that fed on NaTPI-producing (WT) genotypes were lighter and had less gut proteinase activity compared to those that fed on genotypes with either little or no NaTPI activity. Unexpectedly, NaTPI activity in vitro assays not only inhibited the trypsin sensitive fraction of gut proteinase activity but also halved the NaTPI-insensitive fraction in third-instar larvae. Unable to degrade NaTPI, larvae apparently lacked the means to adapt to NaTPI in their diet. However, caterpillars recovered at least part of their gut proteinase activity when they were transferred from NaTPI-producing host plants to NaTPI-free host plants. In addition extracts of basal leaves inhibited more gut proteinase activity than did extracts of middle stem leaves with the same protein content. Conclusions/Significance: Although larvae can minimize the effects of high NaTPI levels by feeding on leaves with high protein and low NaTPI activity, the host plant's endogenous NaTPIs remain an effective defense against M. sexta, inhibiting gut proteinase and affecting larval performance.

Developmental and digestive flexibilities in the midgut of a polyphagous pest, the cotton bollworm, helicoverpa armigera - Sarate, P. J.; Tamhane, V. A.; Kotkar, H. M.; Ratnakaran, N.; Susan, N.; Gupta, Vidya S.; Giri, Ashok P. (Journal of Insect Science, 2012)
Developmental patterns and survival of the cotton bollworm, Helicoverpa armigera Hubner (Lepidoptera: Noctuidae), a polyphagous insect pest, have been studied with reference to the effect of diet on major gut digestive enzymes (amylases, proteases, and lipases). Significant correlations between nutritional quality of the diet and larval and pupal mass were observed when H. armigera larvae were fed on various host plants viz. legumes (chickpea and pigeonpea), vegetables (tomato and okra), flowers (rose and marigold), and cereals (sorghum and maize). Larvae fed on diets rich in proteins and/or carbohydrates (pigeonpea, chickpea, maize, and sorghum) showed higher larval mass and developed more rapidly than larvae fed on diets with low protein and carbohydrate content (rose, marigold, okra, and tomato). Low calorific value diets like rose and marigold resulted in higher mortality (25-35%) of H. armigera. Even with highly varying development efficiency and larval/pupal survival rates, H. armigera populations feeding on different diets completed their life cycles. Digestive enzymes of H. armigera displayed variable expression levels and were found to be regulated on the basis of macromolecular composition of the diet. Post-ingestive adaptations operating at the gut level, in the form of controlled release of digestive enzymes, might be a key factor contributing to the physiological plasticity in H. armigera.
Keywords: amylases; larval performance; Lipases; Proteases

Dynamic proteome in enigmatic preeclampsia: an account of molecular mechanisms and biomarker discovery - Mary, Sheon; Patil, Gouri V.; Kulkarni, Asmita V.; Kulkarni, Mahesh J.; Joshi, Sadhana R.; Mehendale, Savita S.; Giri, Ashok P. (Proteomics Clinical Applications, 2012)
The coevolution of genomics and proteomics has led to advancements in the field of diagnosis and molecular mechanisms of disease. Proteomics is now stepping into the field of obstetrics, where early diagnosis of pregnancy complication such as preeclampsia (PE) is imperative. PE is a multifactorial disease characterized by hypertension with proteinuria, which is a leading cause of maternal and neonatal morbidity and mortality occurring in 5-7% of pregnancies worldwide. This review discusses the probable molecular mechanisms that lead to PE and summarizes the proteomics research carried out in understanding the pathogenicity of PE, and for identifying the candidate biomarker for diagnosis of the disease.
Keywords: Hypertension; Oxidative stress; Pregnancy complication; Proteinuria

Differential protease activity augments polyphagy in helicoverpa armigera - Chikate, Yojana R.; Tamhane, V. A.; Joshi, Rakesh S.; Gupta, Vidya S.; Giri, Ashok P. (Insect Molecular Biology, 2013)
Helicoverpa armigera (Lepidoptera: Noctuidae) and other polyphagous agricultural pests are extending their plant host range and emerging as serious agents in restraining crop productivity. Dynamic regulation, coupled with a diversity of digestive and detoxifying enzymes, play a crucial role in the adaptation of polyphagous insects. To investigate the functional intricacy of serine proteases in the development and polyphagy of H.armigera, we profiled the expression of eight trypsin-like and four chymotrypsin-like phylogenetically diverse mRNAs from different life stages of H.armigera reared on nutritionally distinct host plants. These analyses revealed diet- and stage-specific protease expression patterns. The trypsins expressed showed structural variations, which might result in differential substrate specificity and interaction with inhibitors. Protease profiles in the presence of inhibitors and their mass spectrometric analyses revealed insight into their differential activity. These findings emphasize the differential expression of serine proteases and their consequences for digestive physiology in promoting polyphagy in H.armigera.
Keywords: adaptation; chymotrypsin; Helicoverpa armigera; polyphagy; Trypsin

Differential antibiosis against helicoverpa armigera exerted by distinct inhibitory repeat domains of capsicum annuum proteinase inhibitors - Joshi, Rakesh S.; Gupta, Vidya S.; Giri, Ashok P. (Phytochemistry, 2014)
Plant defensive serine proteinase inhibitors (Pis) are known to have negative impact on digestive physiology of herbivore insects and thus have a crucial role in plant protection. Here, we have assessed the efficacy and specificity of three previously characterized inhibitory repeat domain (IRD) variants from Capsicum annuum PIs viz., IRD-7, -9 and -12 against gut proteinases from Helicoverpa armigera. Comparative study of in silico binding energy revealed that IRD-9 possesses higher affinity towards H. armigera serine proteinases as compared to IRD-7 and -12. H. armigera fed on artificial diet containing 5 TIU/g of recombinant IRD proteins exhibited differential effects on larval growth, survival rate and other nutritional parameters. Major digestive gut trypsin and chymotrypsin genes were down regulated in the IRD fed larvae, while few of them were up-regulated, this indicate alterations in insect digestive physiology. The results corroborated with proteinase activity assays and zymography. These findings suggest that the sequence variations among Pis reflect in their efficacy against proteinases in vitro and in vivo, which also could be used for developing tailor-made multi-domain inhibitor gene(s). (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Capsicum annuum; Helicoverpa armigera; Inhibitory repeat domain; Proteases; Proteinase inhibitors

Development of diagnostic fragment ion library for glycated peptides of human serum albumin: targeted quantification in prediabetic, diabetic, and microalbuminuria plasma by parallel reaction monitoring, SWATH, and MSE - Korwar, Arvind M.; Vannuruswamy, Garikapati; Jagadeeshaprasad, Mashanipalya G.; Jayaramaiah, Ramesha H.; Bhat, Shweta; Regin, Bhaskaran S.; Ramaswamy, Sureshkumar; Giri, Ashok P.; Mohan, Viswanathan; Balasubramanyam, Muthuswamy; Kulkarni, Mahesh J. (Molecular & Cellular Proteomics, 2015)
Human serum albumin is one of the most abundant plasma proteins that readily undergoes glycation, thus glycated albumin has been suggested as an additional marker for monitoring glycemic status. Hitherto, only Amadori-modified peptides of albumin were quantified. In this study, we report the construction of fragment ion library for Amadori-modified lysine (AML), N(epsilon)-(carboxymethyl) lysine (CML)-, and N(epsilon)-(carboxyethyl) lysine (CEL)-modified peptides of the corresponding synthetically modified albumin using high resolution accurate mass spectrometry (HR/AM). The glycated peptides were manually inspected and validated for their modification. Further, the fragment ion library was used for quantification of glycated peptides of albumin in the context of diabetes. Targeted Sequential Window Acquisition of all THeoretical Mass Spectra (SWATH) analysis in pooled plasma samples of control, prediabetes, diabetes, and microalbuminuria, has led to identification and quantification of 13 glycated peptides comprised of four AML, seven CML, and two CEL modifications, representing nine lysine sites of albumin. Five lysine sites namely K549, K438, K490, K88, and K375, were observed to be highly sensitive for glycation modification as their respective m/z showed maximum fold change and had both AML and CML modifications. Thus, peptides involving these lysine sites could be potential novel markers to assess the degree of glycation in diabetes.

Differential accumulation of vimentin fragments in preeclamptic placenta - Mary, Sheon; Kulkarni, Mahesh J.; Mehendale, Savita S.; Joshi, Sadhana R.; Giri, Ashok P. (Cytoskeleton, 2017)
Preeclampsia is a pregnancy complication that is the result of abnormal placentation because of inadequate trophoblast invasion into spiral arteries that prevent normal blood flow to the placenta. We report the alteration in vimentin protein proteolysis in placenta of normotensive and preeclamptic women, which is known to have a role in many physiological functions other than its major function in the structural integrity of the cell. Placental proteome from normotensive (n=25) and preeclamptic pregnancies (n=25) showed eight differentially accumulated protein spots of vimentin (proteolytic fragments) by two-dimensional electrophoresis. Immunoblots of normotensive and preeclamptic placenta revealed a difference in proteolytic processing of vimentin. In particular, lower molecular weight vimentin fragments of 32 and 20 kDa were 3.3 and 2.6-fold (p<0.0001) higher, respectively, in preeclampsia compared with normotensive placenta.

Dynamic metabolic reprogramming of steroidal glycol-alkaloid and phenylpropanoid biosynthesis may impart early blight resistance in wild tomato (Solanum arcanum Peralta) - Shinde, Balkrishna A.; Dholakia, Bhushan B.; Hussain, Khalid; Panda, Sayantan; Meir, Sagit; Rogachev, Ilana; Aharoni, Asaph; Giri, Ashok P.; Kamble, Avinash C. (Plant Molecular Biology, 2017)
Alternaria solani severely affects tomato (Solanum lycopersicum L.) yield causing early blight (EB) disease in tropical environment. Wild relative, Solanum arcanum Peralta could be a potential source of EB resistance; however, its underlying molecular mechanism largely remains unexplored. Hence, non-targeted metabolomics was applied on resistant and susceptible S. arcanum accessions upon A. solani inoculation to unravel metabolic dynamics during different stages of disease progression. Total 2047 potential metabolite peaks (mass signals) were detected of which 681 and 684 metabolites revealed significant modulation and clear differentiation in resistant and susceptible accessions, respectively. Majority of the EB-triggered metabolic changes were active from steroidal glycol-alkaloid (SGA), lignin and flavonoid biosynthetic pathways. Further, biochemical and gene expression analyses of key enzymes from these pathways positively correlated with phenotypic variation in the S. arcanum accessions indicating their potential role in EB. Additionally, transcription factors regulating lignin biosynthesis were also up-regulated in resistant plants and electrophoretic mobility shift assay revealed sequence-specific binding of rSaWRKY1 with MYB20 promoter. Moreover, transcript accumulation of key genes from phenylpropanoid and SGA pathways along with WRKY and MYB in WRKY1 transgenic tomato lines supported above findings. Overall, this study highlights vital roles of SGAs as phytoalexins and phenylpropanoids along with lignin accumulation unrevealing possible mechanistic basis of EB resistance in wild tomato.

Differential modulation in metabolites revealed with the improvement in the shelf-life of alphonso fruits - Dar, M. Saleem; Dholakia, Bhushan B.; Shanmugam, Haripriya; Gupta, Vidya S.; Subramanian, K. S.; Subramanian, J.; Giri, Ashok P. (Molecular Biotechnology, 2020)
Globally farmers have difficulty in extending the shelf-life of the tropical fruits due to their perishable nature. The present study aimed to assess the effect of hexanal nano-formulation treatment (NFT) on the shelf-life of Alphonso mango. Further, volatilomics was performed to explore the molecular basis of such effect. Untreated and treated fruits were sampled starting from 5th to 21st day after NFT at an interval of 4 days. Moderate changes in visual and digital colour parameters were evident from the intact and dissected fruits of NFT set compared to untreated fruits. Biochemical assays affirmed the phenotypic differences with significant changes in the colour imparting compounds like carotenoids and anthocyanins among them. Further, gas chromatography-mass spectrometry analysis revealed significant qualitative and quantitative variations in the different classes of compounds like lactones, furanones, esters, aldehydes and alcohols. Some of the key metabolites showed differential modulations among the NFT and untreated fruit sets indicating their potential role in various processes, which ultimately might have resulted in delayed ripening of the mango. Overall, this study has demonstrated the beneficial effect of hexanal and identified important metabolites with the enhanced shelf-life in Alphonso that could be useful for farmers and mango-based food/flavour industries.
Keywords: Alphonso; GC-MS; Metabolites; Nano-biotechnology; Nano-formulation; Shelf-life; Volatilomics

Discovery of potential multi-target-directed ligands by targeting host-specific SARS-CoV-2 structurally conserved main protease - Joshi, Rakesh S.; Jagdale, Shounak S.; Bansode, Sneha B.; Shankar, S. Shiva; Tellis, Meenakshi B.; Pandya, Vaibhav Kumar; Chugh, Anita; Giri, Ashok P.; Kulkarni, Mahesh J. (Journal of Biomolecular Structure & Dynamics, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has resulted in the current COVID-19 pandemic. Worldwide this disease has infected over 2.5 million individuals with a mortality rate ranging from 5 to 10%. There are several efforts going on in the drug discovery to control the SARS-CoV-2 viral infection. The main protease (M-Pro) plays a critical role in viral replication and maturation, thus can serve as the primary drug target. To understand the structural evolution of M-Pro, we have performed phylogenetic and Sequence Similarity Network analysis, that depicted divergence of Coronaviridae M-Pro in five clusters specific to viral hosts. This clustering was corroborated with the comparison of M-Pro structures. Furthermore, it has been observed that backbone and binding site conformations are conserved despite variation in some of the residues. These attributes can be exploited to repurpose available viral protease inhibitors against SARS-CoV-2 M-Pro. In agreement with this, we performed screening of similar to 7100 molecules including active ingredients present in the Ayurvedic anti-tussive medicines, anti-viral phytochemicals and synthetic anti-virals against SARS-CoV-2 M-Pro as the primary target. We identified several natural molecules like delta-viniferin, myricitrin, taiwanhomoflavone A, lactucopicrin 15-oxalate, nympholide A, afzelin, biorobin, hesperidin and phyllaemblicin B that strongly binds to SARS-CoV-2 M-Pro. Intrestingly, these molecules also showed strong binding with other potential targets of SARS-CoV-2 infection like viral receptor human angiotensin-converting enzyme 2 (hACE-2) and RNA dependent RNA polymerase (RdRp). We anticipate that our approach for identification of multi-target-directed ligand will provide new avenues for drug discovery against SARS-CoV-2 infection. Communicated by Ramaswamy H. Sarma
Keywords: Coronavirus; COVID-19; hACE-2; MPro; multi-target-directed ligand; protease inhibitor; RdRp; SARS-CoV-2 virus

Diversity in chemical structures and biological properties of plant alkaloids - Bhambhani, Sweta; Kondhare, Kirtikumar R.; Giri, Ashok P. (Molecules, 2021)
Phytochemicals belonging to the group of alkaloids are signature specialized metabolites endowed with countless biological activities. Plants are armored with these naturally produced nitrogenous compounds to combat numerous challenging environmental stress conditions. Traditional and modern healthcare systems have harnessed the potential of these organic compounds for the treatment of many ailments. Various chemical entities (functional groups) attached to the central moiety are responsible for their diverse range of biological properties. The development of the characterization of these plant metabolites and the enzymes involved in their biosynthesis is of an utmost priority to deliver enhanced advantages in terms of biological properties and productivity. Further, the incorporation of whole/partial metabolic pathways in the heterologous system and/or the overexpression of biosynthetic steps in homologous systems have both become alternative and lucrative methods over chemical synthesis in recent times. Moreover, in-depth research on alkaloid biosynthetic pathways has revealed numerous chemical modifications that occur during alkaloidal conversions. These chemical reactions involve glycosylation, acylation, reduction, oxidation, and methylation steps, and they are usually responsible for conferring the biological activities possessed by alkaloids. In this review, we aim to discuss the alkaloidal group of plant specialized metabolites and their brief classification covering major categories. We also emphasize the diversity in the basic structures of plant alkaloids arising through enzymatically catalyzed structural modifications in certain plant species, as well as their emerging diverse biological activities. The role of alkaloids in plant defense and their mechanisms of action are also briefly discussed. Moreover, the commercial utilization of plant alkaloids in the marketplace displaying various applications has been enumerated.
Keywords: alkaloid; Biological activity; classification; defense; Enzyme; modification

Dietary influence on modulation of Helicoverpa armigera oral secretion composition leading to differential regulation of tomato plant defense. - Kallure, Gopal S.; Shinde, Balkrishna A.; Barvkar, Vitthal T.; Kumari, Archana; Giri, Ashok P. (Plant Science, 2022)
Little is known about how different plant-based diets influence the insect herbivores' oral secretion (OS) composition and eventually the plant defense responses. We analyzed the OS composition of the generalist Lepidopteran insect, Helicoverpa armigera feeding on the host plant tomato (OSH), non-host plant capsicum (OSNH), and artificial diet (OSAD) using Liquid Chromatography-Quadrupole Time of Flight Mass Spectrometry. Higher numbers and levels of alkaloids and terpenoids were observed in OSH and OSNH, respectively while OSAD was rich in phospholipids. Interestingly, treatment of H. armigera OSAD, OSH and OSNH on wounded tomato leaves showed differential expression of (i) genes involved in JA and SA biosynthesis and their responsive genes, and (ii) biosynthetic pathway genes of chlorogenic acid (CGA) and trehalose, which exhibited increased accumulation along with several other plant defensive metabolites. Specifically, high levels of CGA were detected after OSH and OSNH treatments in tomato leaves. There was higher expression of the genes involved in phenyl-propanoid biosynthesis, which may lead to the increased accumulation of CGA and related metabolites. In the insect bioassay, CGA significantly inhibited H. armigera larval growth. Our results underline the differential accumulation of plant and insect OS metabolites and identified potential plant metabolite(s) affecting insect growth and development.
Keywords: Chlorogenic acid; defense; Metabolites; Non-host; Oral secretion; trehalose

Domain shuffling and site-saturation mutagenesis for the enhanced inhibitory potential of amaranthaceae α-amylase inhibitors - Rane, Ashwini S.; Nair, Vineetkumar S.; Joshi, Rakesh S.; Giri, Ashok P. (Protein Journal, 2023)
Amaranthaceae a-amylase inhibitors (AAIs) are knottin-type proteins with selective inhibitory potential against coleopteran a-amylases. Their small size and remarkable stability make them exciting molecules for protein engineering to achieve superior selectivity and efficacy. In this report, we have designed a set of AAI pro- and mature peptides chimeras. Based on in silico analysis, stable AAI chimeras having a stronger affinity with target amylases were selected for characterization. In vitro studies validated that chimera of the propeptide from Chenopodium quinoa a-AI and mature peptide from Beta vulgaris a-AI possess 3, 7.6, and 4.26 fold higher inhibition potential than parental counterparts. Importantly, recombinant AAI chimera retained specificity towards target coleopteran a-amylases. In addition, to improve the inhibitory potential of AAI, we performed in silico site-saturation mutagenesis. Computational analysis followed by experimental data showed that substituting Asparagine at the 6th position with Methionine had a remarkable increase in the specific inhibition potential of Amaranthus hypochondriacus a-AI. These results provide structural-functional insights into the vitality of AAI propeptide and a potential hotspot for mutagenesis to enhance the AAI activity. Our investigation will be a toolkit for AAI's optimization and functional differentiation for future biotechnological applications.
Keywords: & alpha; -Amylase; -Amylase inhibitors; Amaranthaceae; Coleoptera; Peptide; Pest control

Deciphering the role of metabolites and phytohormones in plant resilience to drought and herbivory - Sahu, Monika; Giri, Ashok P. (Plant Stress, 2025)
<span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Climate change is expected to result in increased variability in precipitation and more frequent outbreaks of insect pests. Thus, it is important to understand how plant-environment interactions are affected by both abiotic and biotic stresses. Water is essential for plant growth, development and interactions with other organisms, including insects. This review synthesizes current studies on the impact of drought and herbivore defense mechanisms and associated metabolic changes in plants. Severe drought can enhance plant tolerance to herbivores by promoting escape strategies whereas mild or intermittent drought may benefit insects by increasing nutrient availability. We discuss how plants adjust their metabolism to mitigate the effects of combined stresses. We further highlight the role of hormonal signaling pathways, such as <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/abscisic-acid" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;">abscisic acid, <a class="topic-link" href="https://www.sciencedirect.com/topics/biochemistry-genetics-and-molecular-biology/jasmonate" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px; font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">jasmonic acid<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">, salicylic acid and ethylene in coordinating plant responses. Research on metabolic changes accompanying hormonal crosstalk involved in managing multiple stresses is still emerging. The available evidence suggests that the outcome of drought and herbivory varies depending on factors such as stress intensity, duration, plant-herbivore species, and insect-feeding guilds. We propose open questions and anticipate further advances in molecular understanding of plant resilience to combined stresses such as drought and herbivory in the near future.